1998
DOI: 10.1063/1.368346
|View full text |Cite
|
Sign up to set email alerts
|

Effects of traps on charge storage characteristics in metal-oxide-semiconductor memory structures based on silicon nanocrystals

Abstract: Charge storage characteristics have been investigated in metal-oxide-semiconductor memory structures based on silicon nanocrystals, where various interface traps and defects were introduced by thermal annealing treatment. The observations demonstrate that traps have strong influence on the charge storage behavior, in which the traps and defects at the internal/surface of silicon nanocrystals and the interface states at the SiO2/Si substrate play different roles, respectively. It is suggested that the injected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
200
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 310 publications
(206 citation statements)
references
References 8 publications
6
200
0
Order By: Relevance
“…This strongly suggests that the loss rate of stored electrons is directly related to the damage induced by irradiation at the Si-substrate/SiO 2 interface (Fig. 24c) as it was initially postulated by Shi (Shi et al, 1998). Previous measurements of electron loss at high temperatures revealed that the long-term retention of the present devices is due to the electron storage in NC traps (Dimitrakis & Normand, 2005).…”
Section: Effects On Charge Retentionsupporting
confidence: 48%
“…This strongly suggests that the loss rate of stored electrons is directly related to the damage induced by irradiation at the Si-substrate/SiO 2 interface (Fig. 24c) as it was initially postulated by Shi (Shi et al, 1998). Previous measurements of electron loss at high temperatures revealed that the long-term retention of the present devices is due to the electron storage in NC traps (Dimitrakis & Normand, 2005).…”
Section: Effects On Charge Retentionsupporting
confidence: 48%
“…Similar mechanism has been observed in silicon based metal-oxide-semiconductor memory where deep traps density in the floating gate governs the charge retention of the device. [20][21][22] In conclusion, OFET-based memory devices with different memory properties were demonstrated by controlling the Ag NPs layer thickness. The 1 nm Ag NP device shows a moderate memory window with 60 V and large on/off current ratio at about 10 5 .…”
Section: -2mentioning
confidence: 99%
“…An interface trap is also useful to extend the current plateau in a single electron pump 4 at low temperatures, which is a promising candidate for a redefinition of ampere to establish a new current standard based on an elementary charge in quantum metrology. On the other hand, charge traps also affect reliability problems 5,6 , such as Random Telegraph Noise (RTN) 7-11 and Negative Bias Temperature Instabilities (NBTI) 12 , causing failures of Static Random Access Memory (SRAM) cells and degradations of long term performance 13,14 . In particular, the impact of RTN is getting more important with the scaling [15][16][17] , since the variations [18][19][20] in an atomic level can affect the drain current in sub-20 nm MOSFETs.…”
mentioning
confidence: 99%